2019
DOI: 10.1109/access.2019.2929522
|View full text |Cite
|
Sign up to set email alerts
|

Freehand, Agile, and High-Resolution Imaging With Compact mm-Wave Radar

Abstract: The aim of this paper is to present a freehand scanning system with a compact mm-wave radar. In order to achieve high-resolution images, the system exploits the free movements of the radar to create a synthetic aperture. However, in contrast to conventional synthetic aperture radar (SAR), in which canonical acquisition surfaces (e.g., planes or cylinders) are used, the system allows for a given tolerance compatible with real handmade trajectories. Moreover, different techniques are studied to compensate for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 29 publications
0
49
0
Order By: Relevance
“…It is interesting to observe that radar data could be merged to create a synthetic aperture radar from arbitrary positions [ 25 , 26 ]. This kind of processing is very powerful as it enables very high resolution images such as the one used for people screening [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is interesting to observe that radar data could be merged to create a synthetic aperture radar from arbitrary positions [ 25 , 26 ]. This kind of processing is very powerful as it enables very high resolution images such as the one used for people screening [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the frequency band selection should be performed, considering the tradeoff between imaging resolution and penetration capabilities and the specific requirements of the practical applications of interest. Despite these powerful approaches for uniform data, last advances in electromagnetic imaging have shown that the use of portable scanners, driven by hand, can be useful for a large number of applications, including electromagnetic compatibility [15], people screening [16], or nondestructive evaluation [17]. However, these systems do not provide equally-spaced acquisition points.…”
Section: Green's Function-based Sar Imaging Methods Of Uniform Measurementioning
confidence: 99%
“…The position of the non-uniform measurement points can be recorded by means of affordable systems, such as depth-cameras [16] or motion capture systems [15,17]. Thus, the above problem becomes how to design the multi-layered C-SAR imaging algorithm once the non-uniform measurement points are known.…”
Section: Introductionmentioning
confidence: 99%
“…This requires integrating a high accuracy real-time positioning system on board the UAV because: (i) the UAV needs accurate positioning to follow the predefined flight path; and (ii) the radar measurements are coherently combined using a Synthetic Aperture Radar (SAR) algorithm, which imposes a geo-referring accuracy several times lower than the smallest working wavelength. Furthermore, the positions of the radar measurements are carefully processed to discard data that could cause unfocusing or resolution degradation in the SAR image (for instance, due to oversampling in some areas [18], since it is very difficult to perform a uniformly sampled acquisition with the UAV). Regarding the processing of the radar data, some improvement steps are also proposed to enhance the resolution and the target discrimination.…”
Section: Introductionmentioning
confidence: 99%